Comparative transcriptome analysis of rumen papillae in suckling and weaned Japanese Black calves using RNA sequencing. (12th May 2018) - Nishihara, Koki; Kato, Daichi; Suzuki, Yutaka; Kim, Dahye; Nakano, Misato; Yajima, Yu; Haga, Satoshi; Nakano, Miwa; Ishizaki, Hiroshi; Kawahara-Miki, Ryouka; Kono, Tomohiro; Katoh, Kazuo; et al.
Abstract: The length and density of rumen papillae starts to increase during weaning and growth of ruminants. This significant development increases the intraruminal surface area and the efficiency of VFA (acetate, propionate, butyrate, etc.) uptake. Thus, it is important to investigate the factors controlling the growth and development of rumen papillae during weaning. This study aimed to compare the transcriptomes of rumen papillae in suckling and weaned calves. Total RNA was extracted from the rumen papillae of 10 male Japanese Black calves (5 suckling calves, 5 wk old; 5 weaned calves, 15 wk old) and used in RNA-sequencing. Transcript abundance was estimated and differentially expressed genes were identified and these data were then used in Ingenuity Pathway Analysis (IPA ) to predict the major canonical pathways and upstream regulators. Among the 871 differentially expressed genes screened by IPA, 466 genes were upregulated and 405 were downregulated in the weaned group. Canonical pathway analysis showed that "atherosclerosis" was the most significant pathway, and "tretinoin, " a derivative of vitamin A, was predicted as the most active upstream regulator during weaning. Analyses also predicted IgG, lipopolysaccharides, and tumor-necrosis factor-α as regulators of the microbe-epithelium interaction that activates rumen-related immune responses. The functional category and the up-regulators found in this study provide a valuable resource for studying new candidate genes related to the proliferation and development of rumen papillae from suckling to weaning Japanese Black calves.